Admissible Estimators in the General Multivariate Linear Model with Respect to Inequality Restricted Parameter Set - Liu Gang; Gui Wenhao; Zhang Shangli (Journal of Inequalities and Applications, 2009)
By using the methods of linear algebra and matrix inequality theory, we obtain the characterization of admissible estimators in the general multivariate linear model with respect to inequality restricted parameter set. In the classes of homogeneous and general linear estimators, the necessary and suffcient conditions that the estimators of regression coeffcient function are admissible are established.